Scooby-Doo! and the groovy ghost - Gelsey, James; Duendes del Sur (Mineapolis, MN : Spotlight, 2013)
Scooby-Doo and his friends investigate when the old Palace Theater develops a guitar-playing ghost just as it is about to be sold to former rock star turned real-estate magnate Stuart Banyon.
Originally published: New York : Scholastic, 2000.
Keywords: Motion picture theaters -- Fiction; Ghosts -- Fiction; Dogs -- Fiction; Mystery and detective stories; Motion picture theaters -- Fiction; Dogs -- Fiction; Ghost stories; Mystery fiction